Pengaruh Debt To Equity Ratio Dan Sales Growth Terhadap Price Book Value Melalui Return On Equity Sebagai Variabel Moderasi - Mawar Ratih Kusumawardani; Brahma Wahyu Kurniawan (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
Company value have important role which is the company increase the value, investors will be more confident and believe in the performance and sustainability of the company's future. An increase in the value of the company will affect the stock price, thats why the company will optimally try to keep stabilize the value of company by give spesial attention to variables that can affect it, such as capital structure, sales growth and profitability. This research aims to determine the effect of debt to equity ratio, sales growth on price book value through return on equity as a moderating variable. This research were pharmaceutical companies listed on the Indonesia Stock Exchange from 2014 to 2020 as a sample with path analysis techniques. The results of this research is debt to equity ratio (X1) has an effect on price book value (Y) so that H1 is accepted, sales growth (X2) has no effect on price book value (Y) so H2 is rejected, sales growth (X1) has an effect on return on equity (Z) so that H3 is accepted, sales growth (X2) has no effect on return on equity (Z) so that H4 is rejected, debt to equity eatio (X1) has no effect on price book value (Y) with return on equity (Z) as a moderating variable so that H5 is rejected, sales growth (X2) has no effect on price book value (Y) with return on equity (Z) as a moderating variable so H6 is rejected.Nilai perusahaan sangat penting bagi perusahaan dimana dengan meningkatnya nilai perusahaan maka investor akan semakian yakin dan percaya atas kinerja dan keberlangsungan masa depan perusahaan. Peningkatan nilai perusahaan akan berpengaruh terhadap harga saham sehingga perusahaan akan berupaya optimal untuk menjaga nilai perusahaan terus stabil dengan memperhatikan variabel-variabel yang bisa mempengaruhi seperti struktur modal, pertumbuhan penjualan dan profitabilitas. Penelitian ini bertujuan untuk mengetahui pengaruh debt to equity ratio, sales growth terhadap price book value melalui return on equity sebagai variabel moderasi. Sampel yang digunakan dalam penelitian ini adalah perusahaan farmasi yang terdaftar di BEI tahun 2014 sampai 2020 dengan teknik analisis jalur (path analysis). Hasil dari penelitian ini adalah debt to equity ratio (X1) berpengaruh terhadap price book value (Y) sehingga H1 diterima,sales growth (X2) tidak berpengaruh terhadap price book value (Y) sehingga H2 ditolak, sales growth (X1) berpengaruh terhadap return on equity (Z) sehingga H3 diterima, pertumbuhan penjualan (X2) tidak perpengaruh terhadap return on equity (Z) sehingga H4 ditolak, debt to equity eatio (X1) tidak berpengaruh terhadap price book value (Y) dengan return on equity (Z) sebagai variabel moderasi sehingga H5 ditolak, sales growth (X2) tidak berpengaruh terhadap price book value (Y) dengan return on equity (Z) sebagai variabel moderasi sehingga H6 ditolak.